Topics in Current Chemistry
DOI: 10.1007/128_2007_128
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry and Photophysics of Coordination Compounds: Copper

Abstract: Cu(I) complexes and clusters are the largest class of compounds of relevant photochemical and photophysical interest based on a relatively abundant metal element. Interestingly, Nature has given an essential role to copper compounds in some biological systems, relying on their kinetic lability and versatile coordination environment. Some basic properties of Cu(I) and Cu(II) such as their coordination geometries and electronic levels are compared, pointing out the limited significance of Cu(II) compounds (d 9 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

27
484
1
13

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 510 publications
(530 citation statements)
references
References 171 publications
27
484
1
13
Order By: Relevance
“…with energetically low-lying π* orbitals, such as aromatic diimines, often display distinct low-energy metal-toligand charge-transfer (MLCT) transitions in the visible part of the spectrum. With this type of electronic excitation, a flattening distortion of the molecular structure takes place.13a, [16][17][18] Such structural rearrangements are usually connected with an increase of non-radiative deactivation or even quenching of the emission due to an increase of the Franck-Condon factors that couple the excited state and the ground state. 19,20 This is especially distinct in non-rigid environments.…”
mentioning
confidence: 99%
“…with energetically low-lying π* orbitals, such as aromatic diimines, often display distinct low-energy metal-toligand charge-transfer (MLCT) transitions in the visible part of the spectrum. With this type of electronic excitation, a flattening distortion of the molecular structure takes place.13a, [16][17][18] Such structural rearrangements are usually connected with an increase of non-radiative deactivation or even quenching of the emission due to an increase of the Franck-Condon factors that couple the excited state and the ground state. 19,20 This is especially distinct in non-rigid environments.…”
mentioning
confidence: 99%
“…Ir or Os) and rare earth metals, which are expensive and environmentally problematic. 12 The luminescence properties of the copper halide clusters arise from a remarkable variety of emissive states, which have been extensively investigated in the last 30 years and can be summarized as follows: (a) a low-energy emission, attributed to a triplet cluster-centered ( 3 CC) excited state, is observed in the case of metal center interactions [13][14][15][16][17][18][19] and is independent of the nature of the ligand engaged in the complex; (b) a highenergy emission, attributed to a triplet halide-to-ligand charge transfer ( 3 XLCT) excited state, may show up in the presence of unsaturated ligands with accessible π-orbitals. 20 Moreover, recent studies have shown that several copper compounds present a thermally activated delayed fluorescence (TADF): Cu(I) halide-bridged compounds with P^N ligands are characterized by (metal + halide)-to-ligand charge transfer ((M + X) LCT) excited states where the low singlet-triplet energy gap allows emission from both the singlet and the triplet excited states, depending on the temperature.…”
mentioning
confidence: 99%
“…4 Indeed, their comparative ease of synthesis has in part driven the widespread success enjoyed by iridium cyclometalates in roles ranging from dopants in OLED displays to sensitizers in photochemical hydrogen production. 5,6 Copper-based luminophores 7 have been investigated as an inexpensive alternative to the more ubiquitous noble metal emitters and recently our group introduced copper(I) amidophosphine complexes as a class of highly luminescent compounds. To date we have focused on binuclear 8 and mononuclear 9 copper(I) complexes that feature tridentate and bidentate arylamidophosphine ligands, respectively.…”
mentioning
confidence: 99%
“…While their quantum efficiencies are not in general as high as those complexes highlighted above, 8,9 they are favorable when compared to other classes of copper emitters. 7 Moreover, their ease of structural variation makes this class of complexes a convenient family for further expansion and study.…”
mentioning
confidence: 99%
See 1 more Smart Citation